Efektivitas Peserta Didik dalam Proses Pembelajaran di SMA Negeri 1 Ngemplak Boyolali - Widya Utami Setyorini; Devi Widya Ningrum (Jurnal Ilmiah Kampus Mengajar, 2021)
Based on the existence of limitations in the teaching and learning proccess and unrealized programs that affect school effectiveness, the purpose of this study is to obtain information about the effective-ness of learning in SMA Negeri 1 Ngemplak, Boyolali. The study uses qualitative research approach with case study method using data analysis models Milles and Huberman. Based on the research findings show that: (1) learning is effective because of the conditioning that is done continuously be-tween the vision and mission of the school in achieving quality education, (2) the existence of readi-ness of teacher in planning learning and teacher’s attitudes and capabilities in provide exemplary the students (3) the success of parents in achieving affective learning the students cannot be separated from their parents upbringing influenced by socio-economic background of the family as well as the intensity of the time spent with the students (4) the awareness of society in school success petrified organize effective learning (5) the shape is done with the cooperation of stackholders to establish communication and involvement in school activities.